Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar IPA Kelas IV SD - Deddy F. Kumolontang (Peneliti.net, 2022)
This study aims to improve science learning outcomes through the application of the Problem Based Learning (PBL) model in the fourth grade of GMIM 2 Tinoor Elementary School. This study uses the Classroom Action Research method with four stages, namely planning, observation and reflection. Data collection techniques were carried out through observation and tests. The technique of data analysis is carried out in a study to draw conclusions from the overall data that has been obtained. The research was carried out in 2 cycles with the results of the analysis of mastery learning in the first cycle only reaching 60.8% and the second cycle reaching 86.4%, which is a satisfactory result. Based on these results, the researcher concludes that the application of the Problem Based Learning model in learning can improve learning outcomes of science subjects in grade IV students of GP Tokin Elementary School